Morphological Changes in Sugarcane Crop Induced by the Plant Growth-Promoting Bacterium Azospirillum brasilense - da Silva Viana, Ronaldo [UNESP]; de Almeida Moreira, Bruno Rafael [UNESP]; Lisboa, Lucas Aparecido Manzani [UNESP]; Junior, Rômulo Sandu [UNESP]; Nogueira, Thiago Assis Rodrigues [UNESP]; de Figueiredo, Paulo Alexandre Monteiro [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Ramos, Sergio Bispo [UNESP] (Springer Nature, 2020)
N fertilizers make the total cost of production of biofuels, sugar and bioelectricity expensive in the sugar-energy industry. Microbes could replace N fertilizers in the nutritional management of sugarcane crop by capturing N2 from the atmosphere. We accordingly conducted this scientific study to investigate the response of sugarcane crop to Azospirillum brasilense. We tested the strain Az-V5 at the doses of 0, 50, 100, 200 and 400 mL ha−1, by spraying it into the planting furrow, 7, 14 and 21 days after crop planting into 20-l pots filled with sieved Rhodic Hapludox, with a loamy texture. In order to examine biologically modulated morphological changes in the host plant material, namely sugarcane variety ‘RB86-7515,’ we harvested and then assessed 90-day-old plants for plant height, stalk diameter, number of tillers, number of leaves, leaf area, tiller length, dry matter of shoots and root dry matter. Sugarcane plants treated with the bioagent 14 and 21 days after crop planting had lower mean values of plant height, number of leaves, leaf area, dry matter of shoots and root dry matter. Therefore, applying A. brasilense into the planting furrow, instead of spraying it on sugarcane leaves, could protect it for a longer period from biotic and abiotic factors influencing cell viability, root colonization and ultimately symbiosis. The conclusion is, therefore, application of A. brasilense into planting furrow is the best environmentally friendly and low-cost strategy to promote growth and development in sugarcane plants at the beginning of their life cycle.
Keywords: Diazotrophic bacteria; N2 biological fixation; Plant–bacteria–atmosphere relationship; Saccharum sp